Immersed tunnel foundation on marine clay improved by sand compaction piles. Issue 2 (17th February 2018) - He, Hongtao; Lin, Yougao; Li, Jianyu; Zhang, Nan
ABSTRACT: The sand compaction pile (SCP) method can be applied to soft marine clay ground that is a reinforcement of composite ground consisting of compacted sand piles and surrounding clay. The application of SCP method in the immersed tunnel of Hong Kong–Zhuhai–Macao Bridge verify SCP method is a robust solution to limit the total settlement and differential longitudinal settlement and to promote smooth transition from immersed tunnel to artificial island. The SCP method has significant settlement reduction effect on marine clay. The SCPs can also function as a drainage path to accelerate the consolidation process in marine clay. It is also found that the consolidation rate of SCP-improved ground is delayed compared with that predicted program which is most probably because of the soil disturbance effect during the installation of SCPs.